Tillering dynamics of Tanzania guinea grass under nitrogen levels and plant densities=Dinâmica de perfilhamento do capim-tanzânia sob doses de nitrogênio e densidades de plantas - Manoel Eduardo Rozalino Santos; Janaina Azevedo Martuscello; Fabrício Paiva de Freitas; Dilermando Miranda da Fonseca; Thiago Gomes dos Santos Braz; Márcia Vitória Santos (Acta Scientiarum: Animal Sciences, 2012)
This study evaluated the influence of nitrogen levels (N) and plant density (D) on the tillering dynamics of Tanzania guinea grass (Panicum maximum Jacq.). Treatments were arranged in a completely randomized block design with 12 treatments and two replicates in a factorial scheme (4 × 3) with four levels of N (0, 80, 160 or 320 kg ha-1 N) and three plant densities (9, 25, and 49 plant m-²). Higher number of tillers was observed in the treatment with 9 plants m-² and under higher levels of N, especially in the second and third generations. Still, the N influenced quadratically the appearance rate of basal and total tillers, which were also affected by plant density and interaction N × D. However, the appearance rate of aerial tiller was not influenced by factors evaluated. The mortality rate of total tiller was influenced quadratically by the nitrogen levels and plant densities. The mortality rate of basal tiller responded quadratically to plant density, whereas the mortality rate of aerial tiller increased linearly with fertilization. Pastures with low or intermediate densities fertilized with nitrogen, presented a more intense pattern of tiller renewal. Objetivou-se com este trabalho avaliar o efeito de doses de nitrogênio (N) e densidades de plantas (D) sobre a dinâmica de perfilhamento do capim-tanzânia (Panicum maximum Jacq.). O delineamento foi em blocos casualizados, com 12 tratamentos e duas repetições em esquema fatorial 4 × 3, com quatro doses de N (0, 80, 160 ou 320 kg ha-1 ano-1) e três densidades de plantas (9, 25 ou 49 plantas m-²). O número de perfilhos foi maior na densidade de 9 plantas m-² e nas maiores doses de N, principalmente na segunda e terceira gerações. O N influenciou quadraticamente as taxas de aparecimento de perfilhos basilares e totais, que também foram influenciadas pela densidade de plantas e pela interação N × D. A taxa de aparecimento de perfilhos aéreos, no entanto, não foi influenciada pelos fatores avaliados. A taxa de mortalidade de perfilhos totais foi influenciada de forma quadrática pelas doses de N e pelas densidades de plantas. A taxa de mortalidade de perfilhos basilares respondeu quadraticamente à densidade de plantas, enquanto a taxa de mortalidade de perfilhos aéreos aumentou de linearmente com a adubação. Pastos implantados em densidades baixas ou intermediárias adubados com nitrogênio apresentam padrão mais intenso de renovação de perfilhos.